The Implementation of Religious Moderation in Educational Institusions in the Contemporary Era - Ferunika; Agus Apriansyah; Wan Jamaluddin; Sudarman; Sulthan Syahril (South Sulawesi Education Development (SSED), 2025)
The digital era has added complexity to this issue. Generation Z, as a generation highly familiar with technology, tends to rely on social media as their primary source of information. This study aims to explore the principles of religious moderation implemented at MAN 1 Bandar Lampung, the challenges faced by MAN 1 Bandar Lampung in applying religious moderation, particularly among Generation Z, and strategies to strengthen the implementation of religious moderation, especially through digital-based approaches. This research employs a descriptive qualitative method. The findings indicate that the application of religious moderation principles at MAN 1 Bandar Lampung reflects the school's serious efforts to teach and instill the values of religious moderation in Generation Z students. Three main aspects of religious moderation— tolerance, balance, and avoidance of radicalization—have been implemented through the Islamic Education (PAI) curriculum, extracurricular activities, and student character- building programs.